2007
DOI: 10.1038/sj.ki.5002014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hemodialysis and peritoneal dialysis survival in The Netherlands

Abstract: Considerable geographic variation exists in the relative use of hemodialysis (HD) vs peritoneal dialysis (PD). Studies comparing survival between these modalities have yielded conflicting results. Our aim was to compare the survival of Dutch HD and PD patients. We developed Cox regression models using 16 643 patients from the Dutch End-Stage Renal Disease Registry (RENINE) adjusting for age, gender, primary renal disease, center of dialysis, year of start of renal replacement therapy, and included several inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
5
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 27 publications
11
119
5
5
Order By: Relevance
“…Patient survival on PD in The Netherlands has somewhat improved over the past 10 years (3). The rate we found corresponds with that found in another national study (21), is higher than rates reported from some American studies (4,7), and is somewhat lower than in Asian studies (22,23).…”
contrasting
confidence: 50%
“…Patient survival on PD in The Netherlands has somewhat improved over the past 10 years (3). The rate we found corresponds with that found in another national study (21), is higher than rates reported from some American studies (4,7), and is somewhat lower than in Asian studies (22,23).…”
contrasting
confidence: 50%
“…25 An earlier Canadian registry-based study showed lower mortality rates among PD-compared with HD-treated patients among an incident cohort of 11,970 people. 13 A recent Dutch registry study 16 showed a substantial benefit to PD in early treatment among younger people without diabetes, with lesser benefit among other groups, with a subsequent change to increased longer term mortality associated with PD. Other groups have attempted comparisons but were limited by small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there have been at least three large national database studies comparing PD and HD survival. [29][30][31] These studies do not significantly affect the overall conclusions of the Vonesh review given earlier, as they essentially build upon the scientific equipoise in this area.…”
Section: Mortality Studies In Dialysis Patients: Are Diabetic Pd Patimentioning
confidence: 99%